Enhancing Good Cooperative Governance at Koperasi Merah Putih Ciambar, Indonesia as a Strategy for Sustainable Economic Development - Nurhayati Nurhayati; Eleonora Sofilda; Erliana Banjarnahor; Naila Nasywa Istiqomah (International Journal of Community Service Implementation, 2026)
Cooperatives represent a vital institutional mechanism for advancing inclusive and sustainable economic development, particularly in rural contexts where financial access and managerial capacity remain limited, yet weak governance systems, inadequate human resources, and the absence of standardized operational frameworks continue to constrain their performance in Indonesia. This study evaluates the effectiveness of a community-based governance capacity-building program implemented at Koperasi Merah Putih, Ciambar Village, Sukabumi, which was designed to strengthen good cooperative governance while supporting the achievement of Sustainable Development Goal 8 on decent work and economic growth. Using a mixed-methods approach, the study combined pre-test and post-test assessments with structured perception surveys administered to cooperative managers, supervisors, and members, and the data were analyzed through descriptive statistics and paired sample t-tests. The findings demonstrate a statistically significant improvement in governance knowledge, with mean scores increasing from 1.69 to 4.23 (p < 0.001), alongside a very high level of participant satisfaction (mean score = 4.62), particularly in terms of training relevance, facilitator competence, and practical applicability. These results indicate that targeted governance interventions can enhance institutional transparency, accountability, and participation, thereby strengthen cooperative sustainability and reinforcing their role as engines of community-based economic growthThese results indicate that targeted governance interventions can enhance institutional transparency, accountability, and participation, thereby strengthen cooperative sustainability and reinforcing their role as engines of community-based economic growth